Alcohol, sponsorship, and new media activation: an investigation of Molson Canadian and the 2014 Olympic Games. (2014) - Geurin, Andrea N.; Gee, Sarah
Beer brand Molson Canadian (MC) was an official supporter of Canada's Olympic team for the 2014 Sochi Games; regarded by many as the pinnacle event for winter sports athletes and teams. This paper investigates the use of social media by MC with respect to Canadian teams and athletes who competed at the 2014 Sochi Winter Olympics. A content analysis of Molson Canadian's Facebook page and Twitter account was conducted from 6 February 2014 to 24 February 2014, spanning the entire time period of the Sochi 2014 Games. Results and discussion highlight the topics and categories MC focussed on in its posts and tweets and the engagement elicited from each type of post. These results shed light on MC's social media sponsorship activation effectiveness. MC's posts/tweets were significantly more focused on reporting informational and promotional content than posts/tweets of an interactive nature, which indicates that MC did not exclusively prompt customer interaction during their Olympic sponsorship, a key finding based on the existing literature on this social media effectiveness.